Efficacy and safety of alemtuzumab over 6 years: final results of the 4-year CARE-MS extension trial. (April 2021) - Coles, Alasdair J.; Arnold, Douglas L.; Bass, Ann D.; Boster, Aaron L.; Compston, D. Alastair S.; Fernández, Óscar; Havrdová, Eva Kubala; Nakamura, Kunio; Traboulsee, Anthony; Ziemssen, Tjalf; Jacobs, Alan; Margolin, David H.; et al.
Background: In the 2-year CARE-MS I and II trials, alemtuzumab 12 mg administered on 5 consecutive days at core study baseline and on 3 consecutive days 12 months later significantly improved outcomes versus subcutaneous interferon beta-1a (SC IFNB-1a) in relapsing–remitting multiple sclerosis patients. Here, we present the final 6-year CARE-MS extension trial results (CAMMS03409), and compare outcomes over 6 years in patients randomized to both treatment groups at core study baseline. Methods: Over a 4-year extension, alemtuzumab patients (alemtuzumab-only) received as-needed additional alemtuzumab (⩾12 months apart) for disease activity after course 2. SC IFNB-1a patients who entered the extension discontinued SC IFNB-1a and received 2 alemtuzumab 12 mg courses (IFN–alemtuzumab), followed by additional, as-needed, alemtuzumab. Results: Through year 6, 63% of CARE-MS I and 50% of CARE-MS II alemtuzumab-only patients received neither additional alemtuzumab nor other disease-modifying therapy, with lasting suppression of disease activity, improved disability, and slowing of brain volume loss (BVL). In CARE-MS I patients (treatment-naive; less disability; shorter disease duration), disease activity and BVL were significantly reduced in IFN–alemtuzumab patients, similar to alemtuzumab-only patients at year 6. Among CARE-MS II patients (inadequate response to prior treatment; more disability; longer disease duration), alemtuzumab significantly improved clinical and magnetic resonance imaging outcomes, including BVL, in IFN–alemtuzumab patients; however, disability outcomes were less favorable versus alemtuzumab-only patients. Safety profiles, including infections and autoimmunities, following alemtuzumab were similar between treatment groups. Conclusion: This study demonstrates the high efficacy of alemtuzumab over 6 years, with a similar safety profile between treatment groups. ClinicalTrials.gov identifiers: NCT00530348; NCT00548405; NCT00930553